Evidence-based decision making for nutrition policy and programme formulation in Ethiopia: A qualitative study exploring barriers and facilitators - Hailu, Solomon Eshetu; Bekele, Tesfaye; Covic, Namukolo; Kuche, Desalegn; Teshome, Beza (American Society for Nutrition, 2020)
Despite much nutrition research conducted in Ethiopia, none has described existing opportunities for synergy or possible missed opportunities to use research to inform policy and program decisions to foster accelerated progress. The study aimed to describe prevailing processes on evidence use in formulating nutrition policy and program decisions and identify potential barriers and opportunities for evidence-based decision-making for nutrition for Ethiopia's context.